Estudo dos métodos de rotina diagnóstica de mastite no leite de éguas - Motta, R. G. [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Langoni, Hélio [UNESP]; Motta, D. G. [UNESP]; Franco, M. M. J. [UNESP]; Almeida, A. C. S. [UNESP]; Perrotti, I. B. M. [UNESP]; Listoni, F. J. P. [UNESP]; Menozzi, B. D. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2011)
Routine diagnosis methods used in bovine mastitis were studied in 55 mares in lactation. The findings of strip cup test, California Mastitis Test-CMT, electronic somatic cell count-CCS, microbiological culture, and in vitro antimicrobial susceptibility profile of isolates were discussed. Streptococcus spp., Staphylococcus spp, and enterobacteria were the most common microorganisms isolated in health and CMT-positive mammary glands. Staphylococcus aureus and Arcanobacterium pyogenes were identified in two mares presenting clinical mastitis. Mean somatic cell count of eight mares without presence of microorganisms in milk was 247.57x10³/mL and 1.621,86x10³/mL in 47 mares with positive microbiological culture. Moderate concordance (63.8%) between positive reactions in CMT (1 to 3+) and microbiological culture was observed. Amicacin (78.9%), ceftiofur (74.7%), sulpha-trimetoprim (69,0%) and norfloxacin (69.0%), were the most effective drugs, while resistance of isolates was mainly observed against penicillin (64.8%), gentamycin (35.2%), azithromycin (35.2%), enrofloxacin (28.2%), and florfenicol (28.2%).
Study of routine diagnosis methods of mastitis in mares
Keywords: égua; mastite; California Mastitis Test; contagem de células somáticas; mare; mastits; etiology; California Mastitis Test; somatic cell count